When the Data Source Writes the Conclusion: Evaluating Agricultural Policies. Issue 9 (1st September 2016) - Desiere, Sam; Staelens, Lotte; D'Haese, Marijke
Abstract: Statistics describe realities, but they also shape them, since they are used to design or support policies. As such accurate statistics are important. Using the agricultural sector in Rwanda as a case study, we demonstrate that dubious statistics can spread quickly. According to data from the Food and Agricultural Organization (FAO), yields have increased by 60 per cent since the implementation of large scale agricultural reforms, while other datasets point towards more modest gains. Yet, estimates in line with those of the FAO dominate the official discourse. We suggest that the discrepancies between datasets may be explained by the difficulties of collecting accurate agricultural statistics combined with an incentive to overestimate yields to show that the reforms have worked.